AB0451 Polymyalgia rheumatica is more severe in female patients: a prospective study. (23rd January 2014) - Muratore, F.; Macchioni, P.; Boiardi, L.; Salvarani, C.
Abstract : Background: Recent data showed a longer-course of corticosteroid (CS) therapy, higher cumulative CS dosage and increased number of relapses in female patients with polymyalgia rheumatica (PMR) than in male (1, 2 ). Objectives: To assess gender-related differences in PMR activity and disease course using clinical, PMR-DAS (3 ), quality of life (QoL) and ultrasonographic (US) evaluation. Methods: All patients with suspected PMR seen at our centre are followed according to a standardized protocol that include clinical examination, determination of laboratory parameters (including ESR, CRP, RF, ACPA test), HAQ questionnaire and US examination of shoulders and hips. All patients are treated with a fixed prednisone start dosage (12.5 mg/day) for four weeks and then tapered according to a standardized protocol. Consecutive patients seen in our rheumatological centre with new onset PMR and followed for at least 6 months were included prospectively during a 5 years period. Results: The study cohort included 85 patients (24 m/61 f). At baseline visit there were no significant differences between male and female in demographic, clinical and laboratory data: age (76.2 ± 6.7 vs 74.6 ± 6.9 years, p ns); disease duration at diagnosis (12.8 ± 19.7 vs 15.3 ± 28.8 weeks, p ns); ERS (55.4 ± 18.9 vs 56.6 ± 24.2 mm/1 st h, p ns); CRP (4.55 ± 2.3 vs 4.1 ± 3.5 mg/dl, p ns); PMR-DAS (36.9 ± 13.3 vs 36.8 ± 15.4 p ns); HAQ (1.7 ± 0.5 vs 1.8 vs 0.5 p ns); systemic symptoms (33.3% vs 45.9% p ns). At diagnosis a greater proportion of female patients showed at least one inflamed structure at US shoulder examination compared to male (100% vs 87%, p=0.004). Table 1 shows the significant differences between male an female at 6 months evaluation. At the end of the follow-up period 21 (87.5%) male and 55 (90.2%) female patients were still on steroid treatment (p ns) at a mean dose of 5.1 ± 5.3 and 5.2 ± 3.7 mg/day (p ns) respectively. Conclusions: At six month evaluation female patients had a more active disease compared to male. Number of relapses/recurrences are higher (but the difference was not significant) among female. At diagnosis only US shoulder examination showed a more severe disease in female compared to male patients. References: Narvaez J, Nolla-Solé JM, Valverde-García J, Roig-Escofet D Sex differences in temporal arteritis and polymyalgia rheumatica. J Rheumatol. 2002 Feb;29(2):321-5 Cimmino MA, Parodi M, Caporali R, Montecucco C Is the course of steroid-treated polymyalgia rheumatica more severe in women? Ann N Y Acad Sci. 2006 Jun;1069:315-21 Leeb BF, Bird HA A disease activity score for polymyalgia rheumatica. Ann Rheum Dis. 2004 Oct;63(10):1279-83 Disclosure of Interest: None Declared